طريقة العقوبة فى تعليم مهارة الكلام - Ixsir Eliya; Ja'far Sodik (UIN Fatmawati Sukarno Bengkulu, 2019)
The way it has a job is to communicate educational goals to a intended person ie pupils in an appropriate way to develop pupils. Punishment is a system or decision implemented for those who work bad and offensive. The effectiveness of the skill of speech appeared in the lightness and speed of expression of ideas and minds, and correct in the choice of words and attractive sentences. The objectives in this research are to find out how the punishment method in teaching speech skill. The result is that the punishment method is very important in teaching the skill of speech. It contains the concept of the method of punishment, the purposes of the method and function of the punishment and the objectives of reading, theories of punishment, and the conditions and how to implement the method of punishment, and advantages and disadvantages in the method of punishment, and the objectives of teaching writing skill, and the process of learning the skill of speech.